2012
DOI: 10.1088/0029-5515/52/12/123013
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of Thomson scattering spectra for non-Maxwellian or anisotropic electron distribution functions

Abstract: Monte Carlo techniques applied to Thomson scattering (TS) power spectrum computation have been extended so as to include non-Maxwellian and anisotropic electron distribution functions (EDFs). First, a simple model has been selected for the spatial (angular) anisotropy of electron velocities (uniformly distributed around an axis of angular symmetry on a cone of semiaperture θ anis), while the energies are distributed according to a lower-hybrid-like model function. Spectra have been computed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…As a further development (also in section 2), the explicit temporal evolution of the scattered electromagnetic fields at the detector position is given, as it is employed to benchmark the new software against its Monte Carlo counterpart and to provide a precise and quantitative measure of the agreement between both approaches. The results of some detailed algebraic comparisons among Doppler frequencies and power spectra reported by other authors and in our preceding works [19][20][21] and the present one are summarized in subsection 2.8: such comparisons are important (albeit, recognizedly, somewhat technical) because, in particular, Doppler frequencies have a critical influence on the power spectra. Section 3 contains the bulk of our work.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…As a further development (also in section 2), the explicit temporal evolution of the scattered electromagnetic fields at the detector position is given, as it is employed to benchmark the new software against its Monte Carlo counterpart and to provide a precise and quantitative measure of the agreement between both approaches. The results of some detailed algebraic comparisons among Doppler frequencies and power spectra reported by other authors and in our preceding works [19][20][21] and the present one are summarized in subsection 2.8: such comparisons are important (albeit, recognizedly, somewhat technical) because, in particular, Doppler frequencies have a critical influence on the power spectra. Section 3 contains the bulk of our work.…”
Section: Introductionmentioning
confidence: 57%
“…The present paper implements new numerical procedures for computing the TS power spectra (and the scattered electromagnetic fields involved) for an arbitrary electron distribution function. It is based on the analytical treatment in [20] and compares its efficiency with the results of the Monte Carlo codes in [19,21]. The analytical formulae used in this work are critically compared with results obtained from other authors and it is shown that they represent a generalization in the case of incoming circularly polarised light, due to the general geometrical set-up considered for the electron-wave interaction.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this section the mathematical formalism used to compare both phenomena in the frequency-domain is presented; it will provide the basis for the comparison in the time-domain in section 3. The steps to be taken closely follow the results for TS in [24][25][26][27]. Excellent monographs on classical electrodynamics and SR exist, which have been instrumental at the starting level of the present research: see, for example, [29,30,35,36].…”
Section: Towards the Tsc-hsr Similarity: Frequency-domain Analytical mentioning
confidence: 94%
“…In previous papers the authors have developed Monte Carlo and analytical methods for the ab-initio computation (in a classical framework, disregarding quantum effects) of TS spectra under very general conditions regarding the electron distribution function, as well as the intensity and the polarization of the incoming laser radiation, for plasma fusion diagnostic applications [24][25][26][27][28]. In the course of these investigations,…”
Section: Introductionmentioning
confidence: 99%